2013
DOI: 10.1177/0021998312473859
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic compression failure mechanisms and dynamic effects of integrated woven sandwich composites

Abstract: Low-velocity dynamic compression tests were performed to reveal the failure mechanism and the energy absorption capacity of the integrated woven sandwich composite. Shear deformations were induced by the tilting of fiber piles in the core of the integrated woven sandwich composite. Ductile load–displacement curves are featured by a long deformation plateau originated from rotations of the core piles. Densification is apparent in the later stage of compression. Stout piles in the core also lead to plastic compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…This sandwich structure has the following advantages: (1) sandwich panel can be produced in a single step, and production time and costs are reduced; (2) top and bottom skins are integrally woven together with the core section, therefore the problem of skin-core delamination is solved; (3) the hollow core section can be filled by several materials and, thus, different capabilities can be given to structure [10]. The 3D IWSC panels provide high strength, low weight, thermal insulation, acoustic damping and high skin-core debonding resistance which is attractive for lightweight structures and have been increasingly used in industries such as marine, road and rail transport, automotive and aircraft industry, war industry, building and construction [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…This sandwich structure has the following advantages: (1) sandwich panel can be produced in a single step, and production time and costs are reduced; (2) top and bottom skins are integrally woven together with the core section, therefore the problem of skin-core delamination is solved; (3) the hollow core section can be filled by several materials and, thus, different capabilities can be given to structure [10]. The 3D IWSC panels provide high strength, low weight, thermal insulation, acoustic damping and high skin-core debonding resistance which is attractive for lightweight structures and have been increasingly used in industries such as marine, road and rail transport, automotive and aircraft industry, war industry, building and construction [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Load fluctuation is observed during the interaction and with the bending and progressive deformation of the cell sheets, the force keeps increasing. This phenomenon is also observed by ) (Xiong, et al, 2012) ( Kılıçaslan, et al, 2013) (Fan, et al, 2014). Notably, the interaction time before that projectile is rebounded from corrugation sandwich panel is extended by increasing layer numbers in lower relative density As to hexagonal honeycomb sandwich panels, increasing layer numbers can not only noticeably lower force values of structures during impact but also prolong interaction time as shown in Figure 13.…”
Section: Effect Of Layer Numbermentioning
confidence: 53%
“…It makes the study of the projectile impact resistance of sandwich components a significant task. Much theoretical, numerical and experimental work in dynamic properties including projectile impact resistance of sandwich structures with cellular cores has been taken (Zhu, et al, 2008;Jing, et al, 2011;Yin, et al, 2013;Ni, et al, 2013;Zhang, et al, 2013;Su, et al, 2013;Fan, et al, 2014;Jiang, et al, 2014;Ebrahimi et al, 2016). Liaghat et al (2010) introduced an analytical model based on energy method to predict the ballistic limit of metallic honeycombs.…”
Section: Introductionmentioning
confidence: 99%
“…11 Low-velocity flatwise compression tests were performed to reveal the dynamic behavior and strain rate effect of WTSCs. 12,13 According to the research, the woven skins of WTSCs are usually not strong enough when bearing load. Li et al 14 revealed compression responses of pyramidal truss core sandwich panels, with Euler macrobuckling, shear macrobuckling of the core, skin microbuckling, skin wrinkling, skin crushing, and other failure modes discussed.…”
Section: Introductionmentioning
confidence: 99%